Examining the temporal impact of stock market development on carbon intensity: Evidence from South Asian countries. (1st November 2021) - Sharma, Rajesh; Shahbaz, Muhammad; Sinha, Avik; Vo, Xuan Vinh
Abstract: The growing size of stock market in the South Asian countries might have contributed to raising the level of industrial production and energy consumption. This upturned energy usage might have widened the scope for carbon emissions because these nations heavily rely on fossil fuels. In this milieu, therefore, in the present study, we assessed the impacts of stock market development, per capita income, trade expansion, renewable energy solutions, and technological innovations on carbon intensity in the four South Asia countries from 1990 to 2016. The empirical results based on the CS-ARDL approach revealed that stock market development, per capita income, and trade expansion invigorated carbon intensity in the South Asian countries. On the contrary, the increased usage of renewable energy solutions and technological advancement helped in reducing the energy-led carbon intensity. Further, the interaction of stock market with renewable energy, and subsequently with technological advancement delivered insignificant coefficients, which indicates the inefficacy of renewable energy and technological advancement in regulating stock market-led carbon intensity during the study period. Therefore, by considering the need for complementarity between economic growth and environmental targets, we proposed a multipronged policy framework, which may help the selected countries to attain the Sustainable Development Goals, with a special focus on SDG 7, 8, 9, and 13. Graphical abstract: The proposed scheme to reduce carbon intensity. Image 1 Highlights: Stock market development contributes to raising energy-led carbon intensity. Per capita income and trade openness intensify carbon intensity. Renewable energy and technological innovation fortify environmental quality. Renewable energy and technological innovation unable to regulate stock market-led carbon intensity.